THE INFLUENCE OF SOCIAL MEDIA MARKETING, ELECTRONIC WORD OF MOUTH AND E-SERVICE QUALITY ON PURCHASE DECISIONS IN BUKALAPAK MARKETPLACE - Meltareza, Ridma; Redyanti, Chela (Universitas Indonesia Membangun (Inaba), 2022)
Bukalapak is one of the E-commerce companies in Indonesia. From the owner of a local shopping brand through its own group which was founded in 2010. Bukalapak's net income in the 2017-2021 period fluctuated and at the end of 2021, it decreased significantly. The purpose of this study was to determine the effect of Social Media Marketing, Electronic Word Of Mouth, and E-Service Quality on Purchase Decisions at the Bukalapak Marketplace in Bandung City. The research method used was quantitative methods with descriptive and verification approaches. The types of data used are primary and secondary data sources. The sampling technique used is purposive sampling with a sample size of 100 respondents. The descriptive results show that Purchase Decision, Social Media Marketing, Electronic Word Of Mouth, and E-Service Quality show the poor category. The results of the Coefficient of Determination Simultaneously the effect of Social Media Marketing, Electronic Word Of Mouth, and E-Service Quality on purchasing decisions is 74.5%, the remaining 25.5% is influenced by other factors and hypothesis testing shows that Social Media Marketing partially has a significant effect on decisions. Purchases with a Sig value of 0.035 < 0.05, Electronic Word Of Mouth partially has no significant effect on purchasing decisions with a Sig value of 0.064 > 0.05, and E-Service Quality partially has a significant effect on purchasing decisions. Social Media Marketing, Electronic Word Of Mouth, and E-Service Quality simultaneously have a significant effect on Purchase Decisions with a Sig value of 0.000 <0.05